Phenomenological Study of Wali's Tomb Pilgrimage: Contestation, Pragmatism and Religious Formalism an Indonesia and Malaysia - Saifuddin, Saifuddin; Baidowi, Ahmad; Jamil, Asyraf (LPPPM STAI Darul Hikmah Bangkalan, 2024)
Even though it is still a long-standing debate within Muslims, visiting the wali’s tomb is still a routine ritual. Pilgrimages to the graves of saints in Indonesia and Malaysia present an interesting phenomenon, because both have different principles in applying the law, Malaysia applies sharia law while Indonesia does not. This research seeks to explore the construction of religious piety identity in the tradition of grave pilgrimages, pilgrim behavior and forms of government intervention in the management of saints' graves in Indonesia and Malaysia. This research is a qualitative-phenomenological research, which will reveal the awareness of experiences, social interactions, motives, actions and meanings of the phenomenon of visiting wali’s tomb in Indonesia and Malaysia. The results of this research are; First, the identity of religious piety in the practice of visiting saints emerged as a result of resistance from the religious purification movement which often condemned the practice of visiting wali’s tomb. Second, religious pragmatism can be seen from the motives of pilgrims who use the wali’s tomb as a means of speeding up the fulfillment of their wishes, as well as syncretic behavior by using the burial ground as a means of carrying out all their affairs. In contrast to Malaysia, in Indonesia, the government tends to be responsive to the management of guardian graves by designing them as part of business and tourism. Third, Malaysia uses a sharia law approach to stem deviant behavior from pilgrimage (khurafat), whereas in Indonesia it does not.